2015
DOI: 10.1111/clr.12601
|View full text |Cite
|
Sign up to set email alerts
|

The genes Scgb1a1, Lpo and Gbp2 characteristically expressed in peri‐implant epithelium of rats

Abstract: The present results suggested that genes Scgb1a1, Lpo, and Gbp2 are characteristically expressed in the PIE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Additionally, inflammatory microenvironment caused by continuous hyperglycemia impacts bone regeneration needed to treat severe bone loss associated with peri‐implantitis. Even though, controlling the level of glucose in plasma could allow a safe implant surgery, but the long term inflammation in these patients due to insulin resistance makes it difficult to control the infection, and reliance on antibiotics is not feasible for the entirety in such cases (Ajami et al., 2016; Bapputty et al., 2019; de Molon et al., 2013; Mori et al., 2016). The lack of knowledge regarding molecular mechanisms leading to this predisposition makes it difficult to plan better intervention strategies (Yu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inflammatory microenvironment caused by continuous hyperglycemia impacts bone regeneration needed to treat severe bone loss associated with peri‐implantitis. Even though, controlling the level of glucose in plasma could allow a safe implant surgery, but the long term inflammation in these patients due to insulin resistance makes it difficult to control the infection, and reliance on antibiotics is not feasible for the entirety in such cases (Ajami et al., 2016; Bapputty et al., 2019; de Molon et al., 2013; Mori et al., 2016). The lack of knowledge regarding molecular mechanisms leading to this predisposition makes it difficult to plan better intervention strategies (Yu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that 1279 upregulated and downregulated genes with >2-fold change were observed in PIE compared with junctional epithelium (JE; Mori et al, 2016). A previous study reported that 1279 upregulated and downregulated genes with >2-fold change were observed in PIE compared with junctional epithelium (JE; Mori et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our microarray analysis showed that 2219 and 2410 genes were upregulated and downregulated with >2‐fold change in PICT compared with PCT and OMCT, respectively. A previous study reported that 1279 upregulated and downregulated genes with >2‐fold change were observed in PIE compared with junctional epithelium (JE; Mori et al, ). The number of expressed genes in PICT was higher than that in PIE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations